Dominican Republic : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Dominican Republic. (IMF Staff Country Reports; Country Report, 2021)
The pandemic interrupted a prolonged growth spell that made the Dominican Republic one of the most dynamic economies in the region amid strong growth, macroeconomic stability and improved social outcomes. This built resilience to the shock-including by maintaining access to markets-and allowed a decisive policy response to address the health emergency, support growth, and protect the vulnerable.